Об игровом подходе к управлению разбегом самолета - Белоусов, А. А.; Грищук, Ф. В.; Кулешин, В. В. (Видавництво Львівської політехніки, 2011)
A game algorithm of control of aircraft engine thrust is suggested, which provides the required velocity rate at the take-off run and takes into account the impact of delay in control designу.
Keywords: динамические игры; летательные аппараты; управление в условиях неопределенности